2011
DOI: 10.1504/ijlt.2011.042646
|View full text |Cite
|
Sign up to set email alerts
|

Deep-play: developing TPACK for 21st century teachers

Abstract: A key complication facing teachers who seek to integrate technology in their teaching is the fact that most technologies are not designed for educational purposes. Making a tool an educational technology requires creative input from the teacher to redesign , or maybe even subvert the original intentions of the designer. The learning technology by design (LT/D) framework has been proposed as being an effective instructional technique to develop deeper understanding of technological pedagogical content knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 28 publications
(14 reference statements)
2
80
1
14
Order By: Relevance
“…One of the important challenges is that the teacher may lack knowledge about teaching approaches using technology [12], [17], [11].Furthermore, the teachers may find it difficult to match existing simulations with their teaching requirements [11] It was found that, if a technology tool such as simulation is applied passively in the classroom, does not improve learning gains [19]. One possible approach to make effective use of simulation for higher learning gains is training of teachers to design their own simulations suitable for their content and pedagogical requirements [15].…”
Section: Need For a Technology Integration Workhopmentioning
confidence: 99%
“…One of the important challenges is that the teacher may lack knowledge about teaching approaches using technology [12], [17], [11].Furthermore, the teachers may find it difficult to match existing simulations with their teaching requirements [11] It was found that, if a technology tool such as simulation is applied passively in the classroom, does not improve learning gains [19]. One possible approach to make effective use of simulation for higher learning gains is training of teachers to design their own simulations suitable for their content and pedagogical requirements [15].…”
Section: Need For a Technology Integration Workhopmentioning
confidence: 99%
“…Este modelo de enseñanza y aprendizaje (E-A), desarrollado por los profesores Punya Mishra y Mattew J. Koehler (2006Koehler ( , 2011 de la Universidad Estatal de Michigan, identifica los tipos de conocimiento que un docente necesita dominar para integrar las Tecnologías de la Información y la Comunicación (TIC) de una forma eficaz en la enseñanza que imparte. Se incluye entre los modelos cognitivos en ambientes cooperativos donde se utiliza la tecnología concretándose en la interacción de los tres elementos que intervienen en la adquisición de conocimientos, esto es: 1) El contenido de la materia concreta que se quiere enseñar; 2) La pedagogía necesaria para que el alumnado alcance esos contenidos; 3) La tecnología que interviene en el proceso de aprendizaje.…”
Section: El Modelo De Enseñanza Y Aprendizaje Tpackunclassified
“…), además debe disponer de la competencia procedimiental y los conocimientos suficientes que le permitan la correcta inclusión de las TIC en clase. En tal sentido, han surgido nuevas aportaciones que inciden en la necesidad de formar al futuro maestro más allá del simple dominio en el uso de las tecnologías (Coronado, 2010;Erdogan & Sahin, 2010;Jang & Chen, 2010;Chai et al, 2011;Koehler et al, 2011;Sahin, 2011;Giménez, 2012;Mudzimiri, 2012;Pamuk, 2012;Jamieson-Porotor et al, 2013;Hubbard et al, 2013;Porras & Salinas, 2013;Cabero, 2014;Ekrem & Recep, 2014;Gómez, 2013). Como ya se ha mencionado, entre estas contribuciones figura el modelo de E-A TPACK (Mishra & Koehler, 2006) que presta especial atención a la correcta incorporación que el futuro docente haga de las TIC en su labor profesional, prestando especial interés en la interacción y la formación del docente en Conocimiento Pedagógico de la Materia (PCK); Conocimiento Tecnológico-Pedagógico (TCK) y Conocimiento Tecnológico de la Disciplina (TPK).…”
Section: Objetivos Y Contextualización De La Investigaciónunclassified
“…In a study conducted with in-service teachers, Madeira (2010) found that "teachers who participated more deeply in the scaffolded reflections were able to understand how their lesson plans and enactment patterns fostered student understanding of relevant science concepts" (p. ii). Graham, Borup, and Smith (2012) (Koehler et al, 2011). In another study, a science methods instructor modeled TPACK teaching while preservice teachers reflected on what they learned about teaching (Hechter & Phyfe, 2010).…”
Section: Learning Activity Typesmentioning
confidence: 99%
“…Archambault and Crippen's (2009) survey measured TPACK among a large group of K-12 online teachers. Schmidt et al (2009) (Lu, Johnson, Tolley, Gillard-Cook, & Lei, 2011;Koehler, Mishra, Bouck, DeSchryver, Kereluik, & Shin, 2011).…”
Section: Self-perception Surveysmentioning
confidence: 99%